Localizing health emergency preparedness and response: emergency medical team development and operations in Pacific island countries and areas - Casey, Sean T; Noste, Erin; Cook, Anthony T; Larsen, Jan-Erik; Cowie, Simon; Ferguson, May M; Beauchemin, Pierre-Yves (Western Pacific Surveillance and Response, 2023)
This article describes the development of national emergency medical teams in Pacific island countries and areas.
Keywords: emergency medical team; disasters; outbreaks; emergency preparedness; Pacific islands; rapid response team